2006
DOI: 10.1007/s00198-006-0213-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of communication in secondary fragility fracture treatment and prevention

Abstract: Communication about events, acuity and clear expectations around roles and follow-up is urgently needed to improve communication throughout the circle of care to support secondary fracture prevention. Fractures from a standing height or similar trauma in women aged 40 to 65 should be treated as suspicious fractures and followed-up to investigate the underlying bone condition. This article reports on challenges and barriers to clear communication among women, their orthopaedic surgeons and family physicians tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Therefore, the way of information transmission is unreliable. A similar problem is reported by Meadows in the Canadian system where a GP is not routinely informed of his/her patient's visit/admission to hospital or of treatment of fragility fracture by an orthopaedic surgeon [23]. Unavailability of diagnostic examinations and specialized therapy, particularly in smaller communities, can be considered as a less significant systemic problem.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the way of information transmission is unreliable. A similar problem is reported by Meadows in the Canadian system where a GP is not routinely informed of his/her patient's visit/admission to hospital or of treatment of fragility fracture by an orthopaedic surgeon [23]. Unavailability of diagnostic examinations and specialized therapy, particularly in smaller communities, can be considered as a less significant systemic problem.…”
Section: Discussionmentioning
confidence: 66%
“…The likelihood that a patient with a fragility fracture perceived themselves to be at increased risk of future fracture was much greater if they had been told that they had osteoporosis. However, the clear communication of an osteoporosis diagnosis to fragility fracture patients is inconsistent, and there is a care gap between the occurrence of a fragility fracture and osteoporosis diagnosis and treatment [ 9 , 10 , 25 ]. Interestingly, the current study demonstrated that only about one in five individuals thought their fracture was related to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps not surprising given the context in which this information was delivered – the fracture clinic. Meadows and colleagues [36] found that the episodic nature of fracture care makes communication among patients, doctors and institutions difficult, if not impossible. The fracture clinic is an extremely busy environment, and patients often do not have the time to absorb all the information they receive, including fracture care, a possible diagnosis of OP and recommendations regarding OP care.…”
Section: Discussionmentioning
confidence: 99%